EVALUASI PENERAPAN AKUNTANSI PAJAK AIR PERMUKAAN PADA PERUSAHAAN DAERAH AIR MINUM KABUPATEN MINAHASA UTARA - Wowor, Stephanie Selina Sheren; Elim, Inggriani; Pangerapan, Sonny (Universitas Sam Ratulangi, 2017)
Surface water tax is one of the local taxes levied by the provincial government as one of the sources of local revenue. Surface water taxes are a tax on the collection and/or utilization of surface water. The objective of this research is to know the use of surface water tax accounting whether the use of surface water tax has been in accordance with applicable laws, tax laws and local regulations. The research was conducted at the Regional Water Supply Company (PDAM) of North Minahasa Regency which is located at Worang By Pass Street Number 1, District Airmadidi. The method used in this research is comparative descriptive method. The results show that the PDAM of North Minahasa Regency calculated and paid a relatively small surface water tax for 2014, 2015 and 2016.Keywords : tax, surface water, evaluation